2016
DOI: 10.12669/pjms.323.9562
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception of educational environment at Aga Khan University Medical College, Karachi, Pakistan

Abstract: Objective:To assess educational environment in Aga Khan University Medical College (AKUMC) by Dundee Ready Educational Environmental Measure (DREEM) scale.Methods:A cross-sectional survey of students at the AKUMC with simple random sampling was carried out from June 2014 till March 2015. Responses in five subscales were used to calculate DREEM scores.Results:The average DREEM score was 125.77±16.8 with a reliability of 91.3%. With regards to subscales, on the 12-item students’ perceptions of learning (PoL) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
7
17
1
Order By: Relevance
“…A study done in Agha Khan University (AKU) medical college, Karachi (which is considered as one of the best medical institute in private sector in Pakistan), total DREEM score was 125.68±18.79 which is comparable to total DREEM score of this study i. 17 A study conducted in six medical institutes from four provinces of Pakistan showed mean DREEM score was 105.0±25.8. In the same study overall DREEM score for male and female students was 98.8±28.9 and 108.6±23.0 respectively.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A study done in Agha Khan University (AKU) medical college, Karachi (which is considered as one of the best medical institute in private sector in Pakistan), total DREEM score was 125.68±18.79 which is comparable to total DREEM score of this study i. 17 A study conducted in six medical institutes from four provinces of Pakistan showed mean DREEM score was 105.0±25.8. In the same study overall DREEM score for male and female students was 98.8±28.9 and 108.6±23.0 respectively.…”
Section: Discussionsupporting
confidence: 67%
“…Sample size came out to be 450. 17 Students were included in the study by simple random method. Roll numbers of all 150 students from each class were written on small pieces of paper and 90 roll numbers were selected randomly by lottery method.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Rehman et al [ 7 ] in 2016, the mean total score on the DREEM was 126/200, which was higher or comparable to those reported by other studies from medical colleges around the world. Based on that score, the bachelor’s medical education program of Aga Khan University in Karachi, Pakistan was categorized as more positive than negative [ 7 ]. Research conducted at an Australian university highlighted that students reported overall positive perceptions of the educational environment, with a high DREEM score of 137.3±18.3.…”
Section: Comparison With Previous Studiessupporting
confidence: 49%
“…Students in this study felt they were being well prepared for their profession. Still, they did not vote in favor of memorization as they believed that there needs to be a focus on applying knowledge rather than memorization (Rehman et al, 2016).…”
Section: Results: Learning Outcomes and Expectations From Studentsmentioning
confidence: 99%
“…Academic ethics: A matter of concern was the students' perception of cheating. Students were mostly neutral about cheating being a problem and did not deter from engaging themselves in academic misconduct (Rehman et al, 2016). A high level of plagiarism was also observed among Pakistani medical students, which may be due to a lack of awareness and consequences (Javaeed et al, 2019).…”
Section: Lack Of Research Trainingmentioning
confidence: 94%